Hybrid silver nanoparticles: Modes of synthesis and various biomedical applications - Priyanka Singh; Shivang Singh; Balaji Maddiboyina; SaiKrishna Kandalam; Tomasz Walski; Raghvendra A. Bohara (Electron)
Abstract In the present day, there is a growing trend of employing new strategies to synthesize hybrid nanoparticles, which involve combining various functionalities into a single nanocomposite system. These modern methods differ significantly from the traditional classical approaches and have emerged at the forefront of materials science. The fabrication of hybrid nanomaterials presents an unparalleled opportunity for applications in a wide range of areas, including therapy to diagnosis. The focus of this review article is to shed light on the different modalities of hybrid nanoparticles, providing a concise description of hybrid silver nanoparticles, exploring various modes of synthesis and classification of hybrid silver nanoparticles, and highlighting their advantages. Additionally, we discussed core‐shell silver nanoparticles and various types of core and shell combinations based on the material category, such as dielectric, metal, or semiconductor. The two primary classes of hybrid silver nanoparticles were also reviewed. Furthermore, various hybrid nanoparticles and their methods of synthesis were discussed but we emphasize silica as a suitable candidate for hybridization alongside metal nanoparticles. This choice is due to its hydrophilic surface qualities and high surface charge, which provide the desired repulsive forces to minimize aggregation between the metal nanoparticles in the liquid solution. Silica shell encapsulation also provides chemical inertness, robustness and the adaptability to the desired hybrid nanoparticle. Therefore, among all the materials used to coat metal nanoparticles; silica is highly approved.